Fine Tuning the Cytokine Storm by IFN and IL-10 Following Neurotropic Coronavirus Encephalomyelitis - Savarin, Carine; Bergmann, Cornelia C. (Frontiers in Immunology, 2018)
The central nervous system (CNS) is vulnerable to several viral infections including herpes viruses, arboviruses and HIV to name a few. While a rapid and effective immune response is essential to limit viral spread and mortality, this anti-viral response needs to be tightly regulated in order to limit immune mediated tissue damage. This balance between effective virus control with limited pathology is especially important due to the highly specialized functions and limited regenerative capacity of neurons, which can be targets of direct virus cytolysis or bystander damage. CNS infection with the neurotropic strain of mouse hepatitis virus (MHV) induces an acute encephalomyelitis associated with focal areas of demyelination, which is sustained during viral persistence. Both innate and adaptive immune cells work in coordination to control virus replication. While type I interferons are essential to limit virus spread associated with early mortality, perforin and interferon-γ promote further virus clearance in astrocytes/microglia and oligodendrocytes respectively. Effective control of virus replication is nonetheless associated with tissue damage, characterized by demyelinating lesions. Interestingly, the anti-inflammatory cytokine IL-10 limits expansion of tissue lesions during chronic infection without affecting viral persistence. Thus, effective coordination of pro- and anti-inflammatory cytokines is essential during MHV induced encephalomyelitis in order to protect the host against viral infection at a limited cost.